The Metastases of Enjoyment: Psychoanalysis, Ethics and the Critique of Ideology - Žukauskaitė, Audronė (Problemos, 1999)
The principle of enjoyment which is the object of our present investigations can be described by constant “sliding of meaning”, caused not only by the polysemy of this concept but also by its dissemination in different areas of theoretical discourse. On the one side, the principle of enjoyment as it is formulated in the field of psychoanalysis, is displaced into the fields of ethics and ideology; this means that ethics and ideology become the object of psychoanalytical investigation. On the other side, the principle of enjoyment removes from the strictly psychoanalytical context and becomes the universal principle which organizes the structural frame of ethical and ideological discourse. In both cases these displacements or metastases signify an irreversible process: the enjoyment organizing different theoretical fields cannot be defined and explained in these fields. The enjoyment means unbearable and traumatic kernel of “the real”, which conditions the symbolic universum of psychical, ethical, and ideological work, but cannot be incorporated by this universum.